O USO DE SIMULAÇÕES E ANIMAÇÕES COMPUTACIONAIS NO ESTUDO DE CONSERVAÇÃO DE ENERGIA MECÂNICA - Bisognin, Vinícius (2014)
Computational resources have been identified as important auxiliary teaching, in view of the current technological developments. Thus, the purpose of this study demand through the use of computational simulations and animations to provide high school students an understanding of the more general principle of Conservation of Mechanical Energy. Learning activities with the use of computational simulations and animations are structured according to the methodology of Three Pedagogical Moments (TMP) and will make use of a Blog as a Virtual Learning Environment (VLE) to provide greater interaction between students and teacher and between them and the simulations and animations. It is expected that the learning of physics concepts involved in the subject of Mechanical Energy Conservation is enhanced.